Genotyping and Phylogenic tree of Toxoplasma gondii in one-humped camels (Camelus dromedarius) in Al- Diwaniyah province in Iraq - Hassan, Taif Hillal; Jarad, Noor Idan (South Eastern European Journal of Public Health, 2024)
The current study is carry out in Al- Diwaniyah province; in Iraq between (September 2023 - March 2024) for determine the seroprevalence of Toxoplasma gondii in camels and molecular identification with phylogenetic analysis. (140) blood and tissue samples were collected from camels from the slaughter of the Al-Diwaniyah province. The results of total serological prevalence showed that 72 (51.42%) of the camels were infected. Genomic DNA was extracted from 140 camel’s tissues samples and SAG3 gene was amplified by PCR. PCR results showed that camels tissues samples 55/140 (39.28 %) have SAG3 gene. Ten PCR positive products of local Toxoplasma gondii isolates were DNA sequencing and compared with other isolates in GenBank. After that, the phylogenetic relationship was analyzed for this parasite using phylogenetic UPGMA tree (MEGA X version). Sequencing and phylogenetic results of Toxoplasma gondii isolate (No.1, 3, 5, 6, and 10) were showed closed genetic related into Toxoplasma gondii genotype I. The camels T. gondii isolates (No.7) were showed closed genetic related into Toxoplasma gondii genotype II. Whereas, the camels T. gondii (No.2, 4, 8, and 9) were showed closed genetic related into Toxoplasma gondii genotype III. At total genetic change (0.01). The homology sequence identity between local The Toxoplasma gondii isolates and NCBI-BLAST related genotype of T. gondii were reveals that genetic homology sequence identity was ranged (99.32% - 100%).